Presuppositions Used by Yang Jong Hoon in Law School - Alessandra Virginia Manurung; Aylanda Hidayati Dwi Nugroho (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study investigates the presuppositions in Yang Jong Hoon’s utterances in the series